“Uttarakuru Dvipa” from the Traiphum Phra Ruang (Three Worlds According to King Ruang) in Pongsakorn’s Novel “Lookmai-Lai-Sonthaya”: Its Creation and Implication - บุญฮก ศรัณย์ภัทร์ (Journal of Social Sciences and Humanities Research in Asia, 2019)
The objective of the study aimed at exploring the literary techniques of using “Uttarakuru Dvipa” from the Traiphum Phra Ruang (Three Worlds Accordting to King Ruang) to the creation of the novel “Lookmai-Lai-Sonthaya,” a novel dealing with mysterious and supernatural elements by Pongsakorn, and analyzing important implication of Uttarakuru Dvipa depicted in this novel. It was found from the study that Pongsakorn had applied details of Uttarakuru Dvipa from Traiphum Phra Ruang to the novel, portraying this ideal piece of land through creating the novel’s elements, which were the application of the conflict during investigation overlapped by Uttarakuru Dvipa, the creation of the male protagonist from Uttarakuru Dvipa and the creation of scenes combined between the two worlds. All of these were to compare different ethics levels between the two worlds, leading to the main theme, which was the fact that “desires were the cause of all problem.” This was for the people in Jambu Dvipa to let go of their desires. Inserting the idea of Uttarakuru Dvipawas also important to the novel in terms of emphasizing the otherness between the two worlds. It was the otherness caused by the emphasis on the totally contrasting ethics levels between people in Jambu Dvipa and those in Uttarakuru Dvipa. The novel ended with the togetherness of the characters from the two worlds; however, it was the togetherness with limitations of space and time, in order to highlight the fact that love was only the starting point of the real togetherness in Uttarakuru Dvipa.